The Study Of Clinical Outcomes And Factors Affecting Drug Therapy And Osteoporotic Condition In Chronic Kidney Disease (CKD) Patient In Three Tertiary Hospitals In Pakistan - Tariq, Muhammad Haseeb (2022)
Chronic Kidney Disease (CKD) is associated with several complications including osteoporosis. This study was aimed to determine prevalence of osteoporosis and clinical outcomes along with knowledge, attitude and practices (KAP) of physicians and pharmacist. Prospective quantitative research including cross-sectional and longitudinal study was used to meet the objectives. 196 and 412 CKD patients were studied to determine the prevalence of osteoporosis and clinical outcomes respectively. The KAP of 400 physicians was assessed using CKD-KAP questionnaire which was developed and validated. The knowledge regarding CKD was also determined among 183 pharmacists. Prevalence of osteoporosis and osteopenia was found to be 26.5% and 40.8%, respectively. A reduction of 0.58% in eGFR was observed accounting to poor clinical outcomes.